Sex‐Specific Variation in Foraging Behavior is Related to Telomere Length in a Long‐Lived Seabird - Mauricio Guillen‐Parra; Rocio Barcenas‐Flores; Alberto Velando; Anne Wiley; Bibiana Montoya; Roxana Torres (Ecology and Evolution)
ABSTRACT Foraging during breeding is a demanding activity linked to breeding investment and possibly constrained by individual quality. Telomere length, the protective nucleoproteins located at the ends of the chromosomes, is considered a trait reflecting somatic maintenance and individual quality. Therefore, foraging effort and parental investment may be positively related to telomere length, if individuals with longer telomeres are of better quality and thus able to maintain better body condition and allocate more resources to parental activities. In the brown booby (Sula leucogaster), we investigated if telomere length is related to body mass (a proxy of condition) and whether variation in foraging behavior and provisioning effort is related to telomere length or body mass. Then, we explored whether variation in foraging and provisioning influences the chick mass growth rate. In 34 pairs nesting in Isla de San Jorge, in the Gulf of California, México, we sampled their blood to estimate telomere length, measured their body mass, and for 10 days, recorded their foraging behavior via global positioning system (GPS) loggers and their chick provisioning rate and chicks' mass growth rate. We found a positive relationship between parents' body mass and telomere length. Body mass did not affect foraging behavior. Females with longer telomeres were more prone to travel longer distances toward offshore and deeper waters than females with shorter telomeres. In contrast, males with longer telomere lengths performed more nearshore foraging trips than males with shorter telomeres. The chick provisioning rate was unrelated to telomere length or body mass, but females fed the chick at a rate 2.4 times greater than males. Females' offshore foraging, but not males', was positively related to chick mass growth rate. Our results suggest that individual quality, indicated by telomere length, is an important driver of sex‐specific, between‐individual variation in foraging behavior, indirectly affecting offspring condition.